“IMPLEMENTACIÓN DE BENEFICIOS EN LA LEY ORGÁNICA DE MOVILIDAD HUMANA PARA QUE LOS INMIGRANTES OCUPEN CARGOS PÚBLICOS DE MANERA INMEDIATA. - QUEZADA TOLEDO, DANIELA PATRICIA (2021)
This research, which is detailed under the thesis modality, refers to a legal problem that deserves to be transformed to solve and overcome the socio-legal problem identified in article 49 of the Organic Law of Human Mobility, which stipulates that foreign persons who reside in Ecuador will have the right to vote and be elected to public office provided they have legally resided in the country for five years, this limits the right for these people to work freely and immediately in the public sector, since many of them They have a good profile and preparation in activities and professions that do not exist in Ecuador. For this reason, it is necessary to reform the Organic Law of Human Mobility, article 49, so that these people can immediately occupy public positions in matters of eminent social, academic and scientific need.